The Legitimacy of Electronic Trading Contracts According to the Civil Code - Dahris Siregar; Afni Nirmala Deli Lase; Aguswina Hulu; Berkat Jaya Zendrato; Dina Rizka Yusra; Juwita Mentari; Suriati Lafau; Dahlia Kusuma Dewi (PT Inovasi Pratama Internasional, 2022)
The rapid development in the world of technology has made many changes in every country, especially for the business world in the trade sector. With today's technology, a lot of trade is carried out through the internet or electronic media, so the procedures for trade are also developing in establishing a cooperative process such as an agreement between the parties to agree to hold a transaction. Electronic contracts are one of the new forms of contracts that receive special protection in Law Number 11 of 2008 concerning Electronic Information and Transactions (hereinafter referred to as the ITE Law), especially through Article 1 number 17. The research method used is the normative method, which examines and analyzes the subject matter with the substance of the legislation. The approach method used is a statutory approach and a deductive approach, namely an approach by reasoning from general circumstances to special circumstances. The results and discussion, namely the Validity of Electronic Trading Contracts according to the Civil Code and the Legal Consequences of Illegally Made Electronic Trading Contracts, is that in principle the validity of an agreement is not determined by the physical form of the agreement.